Building a thriving academic hospitalist workforce: A rapid qualitative analysis identifying key areas of focus in the field. Issue 4 (6th March 2023) - Kulkarni, Shradha A.; Keniston, Angela; Linker, Anne S.; Astik, Gopi J.; Kangelaris, Kirsten N.; Leykum, Luci K.; Sakumoto, Matthew; Auerbach, Andrew; Burden, Marisha
Abstract: Background: The hospitalist workforce has been at the forefront of the pandemic and has been stretched in both clinical and nonclinical domains. We aimed to understand current and future workforce concerns, as well as strategies to cultivate a thriving hospital medicine workforce. Design, Setting, and Participants: We conducted qualitative, semistructured focus groups with practicing hospitalists via video conferencing (Zoom). Utilizing components from the Brainwriting Premortem Approach, attendees were split into small focus groups and listed their thoughts about workforce issues that hospitalists may encounter in the next 3 years, identifying the highest priority workforce issues for the hospital medicine community. Each small group discussed the most pressing workforce issues. These ideas were then shared across the entire group and ranked. We used rapid qualitative analysis to guide a structured exploration of themes and subthemes. Results: Five focus groups were held with 18 participants from 13 academic institutions. We identified five key areas: (1) support for workforce wellness; (2) staffing and pipeline development to maintain an adequate workforce to match clinical growth; (3) scope of work, including how hospitalist work is defined and whether the clinical skillset should be expanded; (4) commitment to the academic mission in the setting of rapid and unpredictable clinical growth; and (5) alignment between the duties of hospitalists and resources of hospitals. Hospitalists voiced numerous concerns about the future of our workforce. Several domains were identified as high‐priority areas of focus to address current and future challenges. Abstract :